Internet‐based interventions for cancer‐related distress: exploring the experiences of those whose needs are not met. Issue 4 (17th November 2013) - Gorlick, Amanda; Bantum, Erin O'Carroll; Owen, Jason E.
Abstract Objective Low levels of engagement in Internet‐based interventions are common. Understanding users' experiences with these interventions is a key to improving efficacy. Although qualitative methods are well‐suited for this purpose, few qualitative studies have been conducted in this area. In the present study, we assessed experiences with an Internet‐based intervention among cancer survivors who made minimal use of the intervention. Methods Semi‐structured interviews were conducted with 25 cancer survivors who were minimally engaged (i.e., spent around 1 h total on website) with the online intervention, health‐space.net. The intervention was a 12‐week, facilitated support group with social and informational components. Interviews were analyzed using an interpretive descriptive design. Results Three broad categories, consisting of 18 specific themes, were identified from the interviews, which included connecting with similar others, individual expectations, and problems with the site (Κ = 0.88). The 'similar others' category reflected the significance of interacting with relatable survivors (i.e., same cancer type), the 'individual expectations' category reflected the significance of participants' expectations about using online interventions (i.e., personally relevant information), and the 'problems with the site' category reflected the significance of study procedures (i.e., website structure). Conclusions The data indicate that minimally engaged participants have high variability regarding their needs and preferences for Internet‐based interventions. Using qualitative methodologies to identify and incorporate these needs into the next generation of interventions has the potential to increase engagement and outcomes. The current study provides a foundation for future research to characterize survivors' needs and offer suggestions for better meeting these needs. Copyright © 2013 John Wiley & Sons, Ltd.